2019
DOI: 10.1167/iovs.19-27979
|View full text |Cite
|
Sign up to set email alerts
|

Cone Structure Persists Beyond Margins of Short-Wavelength Autofluorescence in Choroideremia

Abstract: Citation: Foote KG, Rinella N, Tang J, et al. Cone structure persists beyond margins of short-wavelength autofluorescence in choroideremia. Invest Ophthalmol Vis Sci. 2019;60:4931-4942. https://doi.org/10.1167/ iovs.19-27979 PURPOSE. We studied the relationship between structure and function of the choriocapillaris (CC), retinal pigment epithelium (RPE), and photoreceptors in patients with choroideremia (CHM). METHODS.Six CHM patients (12 eyes) and four normal subjects (six eyes) were studied with fundus-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 68 publications
2
15
0
Order By: Relevance
“… 51 According to the authors, this could indicate preserved metabolic activity in the photoreceptors. Pfau and colleagues 52 found preserved light sensitivity in border regions within the atrophic areas of GA, whereas Foote and colleagues 53 demonstrated similar results in patients affected by choroideremia. The border regions within atrophic areas of GA and choroideremia also show short FLIO lifetimes, as has been shown in previous FLIO studies.…”
Section: Discussionmentioning
confidence: 92%
“… 51 According to the authors, this could indicate preserved metabolic activity in the photoreceptors. Pfau and colleagues 52 found preserved light sensitivity in border regions within the atrophic areas of GA, whereas Foote and colleagues 53 demonstrated similar results in patients affected by choroideremia. The border regions within atrophic areas of GA and choroideremia also show short FLIO lifetimes, as has been shown in previous FLIO studies.…”
Section: Discussionmentioning
confidence: 92%
“…Epithelial-mesenchymal transformation (EMT) plays an indispensable role in oxidative stress, stem cell differentiation, growth, and wound healing, but also promotes the occurrence and development of cell fibrosis and cancer pathologies [ 5 , 6 ]. Previous studies confirmed that EMT of RPE cells mediated by transforming growth factor beta 1 (TGF-β1) is the main reason for pathological changes associated with PVR [ 7 , 8 ]. RPE cells convert from an epithelial to mesenchymal phenotype and participate in EMT [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 98%
“…The name of the disease suggests primary involvement of the choroid 5 , a vascularized support structure for the outer retina. For example, choriocapillaris degeneration has been linked with declining visual function in choroideremia 6 . However, several studies have suggested that choroideremia primarily affects the retinal pigment epithelial (RPE) cells 7 – 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Adaptive optics (AO) retinal imaging 31 has provided cellular-level resolution of the living human retina in patients with choroideremia, particularly for assessing the status of cone photoreceptors 6 , 9 , 32 , 33 . Structurally, well-preserved cone photoreceptors have been reported at the margins of RPE atrophy 16 , 33 but areas of reduced cone density elsewhere have also been observed 9 , 16 , 32 .…”
Section: Introductionmentioning
confidence: 99%